Pendampingan Penguatan Ekonomi Kreatif Perempuan Desa Tamansari Wonorejo Kabupaten Pasuruan - Dewi Masita (LP3M IAIFA Kediri, 2024)
The aim of this assistance is to quickly start empowering women's creative economy evenly in the villages of Pasuruan district. The approach used to build the strength and potential of Tamansari village women in a sustainable manner, in this case how to empower Tamansari Village women, is the Asset Based Community Development (ABCD) approach, which is a service approach that empowers the assets owned by a community. The results of the implementation of the creative socio-economic strengthening program for women in Tamansari village are very influential in increasing human resources, creativity and welfare of women in Tamansari village and its surroundings, and changes in society that are more solid and have a positive image towards social change.